2012
DOI: 10.1007/s11547-012-0866-y
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial and nonbronchial systemic artery embolization in managing haemoptysis: 31 years of experience

Abstract: BAE and NBAE are effective and safe for acute treatment of haemoptysis, with low recurrence and complication rates. Interventional radiologist experience is crucial to the successful haemoptysis control and preventing complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 28 publications
2
9
1
1
Order By: Relevance
“…Major complications are rare (< 1%) and include dissection of a bronchial artery, bronchial arterial perforation by a guidewire, transient quadriplegia, transient ischaemic attack, stroke or disseminated infection [ 52 ]. Minor complications are more common (30%) and include chest pain, dysphagia and fever [ 53 ].…”
Section: Bronchial Artery Embolizationmentioning
confidence: 99%
“…Major complications are rare (< 1%) and include dissection of a bronchial artery, bronchial arterial perforation by a guidewire, transient quadriplegia, transient ischaemic attack, stroke or disseminated infection [ 52 ]. Minor complications are more common (30%) and include chest pain, dysphagia and fever [ 53 ].…”
Section: Bronchial Artery Embolizationmentioning
confidence: 99%
“…Mild hemoptysis is known to be easily subsided when underlying disease is treated . On the other hand, in moderate hemoptysis, the most critical aspect is the difficulty maintaining an acceptable level of interpersonal relationships and the psychological implications of this call for an effective therapeutic solution . And moderate hemoptysis usually should be distinguished by quantifying daily bleeding amount, and flexible bronchoscopy (FB) is recommended when hemoptysis persists during treatment of underlying disease .…”
Section: Introductionmentioning
confidence: 99%
“…In our study, success achieved in 90.4% of our patients. The last two retrospective studies have reported 96% success rate in the control of hemoptysis after BAE [11,12].…”
Section: Discussionmentioning
confidence: 99%